Linking Diabetes and Dyslipidemia: Hospital-Based Evidence from Haryana - Umesh Kumar Sharma; Anuradha Jayaraman (The Bioscan, 2024)
Diabetes mellitus is frequently accompanied by dyslipidemia, a major risk factor for cardiovascular complications. This hospital-based cross-sectional study from Faridabad, Haryana, examined 947 patients with type 2 diabetes mellitus (T2DM) to assess the prevalence and patterns of dyslipidemia. The findings revealed a higher occurrence of lipid abnormalities in urban populations compared to rural groups. Low HDL-C, elevated LDL-C, and hypertriglyceridemia were the most common abnormalities, with notable gender-specific differences. These results underscore the importance of early lipid screening, lifestyle interventions, and effective management strategies to reduce long-term complications in T2DM patients.